Tramas da criação participativa: a experiência comunicativa nas obras de Elida Tessler e Beth Moysés - Araujo, Maria Eunice Azambuja de (2018)
The present research is the result of studies of the creative processes of the contemporary process art works by Elida Tessler and Beth Moysés, which modify over time, tending towards the unfinished and coinciding with the life of the artist. Art works that are constituted by the participation of people in its process, with the proposition of actions and the activation of experiences, whose sensorial aesthetic is completed by the action of the spectator, requiring a more active reception. The research was carried out through the observation of a diversity of documents of creative processes so to formulate hypothesis about the main knots of the creation networks studied. For this purpose, the theory of creation processes conceived by Cecília Almeida Salles was used as an instrument for the critique of the processes and as an itinerary for the study and understanding of the art works. The aim of the research is to analyze the communicational aspects of practices that exceed the relation artist spectator and integrate people in their processes, creating a collaboration structure. The objective is to understand the artistic-creative procedures that unleash processes of singularization, collectivization and acting in networks